Analisis Hidrolika dan Perencanaan Tinggi Jagaan (Freeboard) Jembatan Kereta Api (BH-102 KM. 53 + 778) pada Sungai Way Tipo Bekri Kabupaten Lampung Tengah - Elvida, Maharani; Arifaini, Nur; Tugiono, Subuh; Zakaria, Ahmad (Universitas Lampung, 2023)
The planning of a railway bridge over the river is carried out by analyzing the hydraulic factors on the river in accordance with PM No. 60 of 2012 concerning Technical Requirements for Railway Lines. Hydrological and hydraulics analysis was carried out using the HSS Nakayasu method and the HEC-RAS v5.0.7 application program. This study aims to analyze the height of the flood water level based on hydraulic factors on the Way Tipo River and to design a guard height limit (freeboard) railway bridge based on the previously calculated water surface elevation results. Hydraulic analysis and high maintenance planning (freeboard) railway bridge (BH-102 KM. 53 + 778) on the Way Tipo Bekri River, Central Lampung Regency, resulting in flood discharge values for 50 and 100 year return periods of 742,281 m respectively3/s and 854,431 m3/s, the flood water level (MAB) is +45,38 m and +45,51 m, as well as the freeboard the length of the bridge is 1,32 m for the 50 year return period and 1,19 m for the 100 year return period in terms of the difference between the flood water level and the bottom girder of the bridge. It was concluded thatfreeboard The obtained railroad bridge meets the planning criteria, namely at least 1 meters from the bottom girder of the bridge to the flood water level.Key words : railway bridge, hydrology, hydraulics, HSS Nakayasu, HEC-RAS. Perencanaan jembatan kereta api di atas sungai dilakukan dengan menganalisa faktor hidrolika pada sungai sesuai dengan PM No.60 Tahun 2012 tentang Persyaratan Teknis Jalur Kereta Api. Analisis hidrologi dan hidrolika dilakukan menggunakan metode HSS Nakayasu dan program aplikasi HEC-RAS v5.0.7. Penelitian ini bertujuan untuk menganalisis tinggi muka air banjir berdasarkan faktor hidrolika pada Sungai Way Tipo serta merancang batas tinggi jagaan (freeboard) jembatan kereta api berdasarkan hasil elevasi muka air yang telah dihitung sebelumnya. Analisis hidrolika dan perancangan tinggi jagaan (freeboard) jembatan kereta api (BH-102 KM. 53 + 778) pada Sungai Way Tipo Bekri Kabupaten Lampung Tengah menghasilkan nilai debit banjir untuk kala ulang 50 dan 100 tahun masing-masing sebesar 742,281 m3/s dan 854,431 m3/s, elevasi muka air banjir (MAB) sebesar +45,38 m dan +45,51 m, serta nilai freeboard jembatan adalah 1,32 m untuk kala ulang 50 tahun dan 1,19 m untuk kala ulang 100 tahun ditinjau dari selisih antara elevasi muka air banjir dengan gelagar terbawah jembatan. Disimpulkan bahwa freeboard jembatan kereta api yang diperoleh sudah memenuhi kriteria perencanaan yaitu minimal 1 meter dari gelagar terbawah jembatan terhadap muka air banjir. Kata kunci : jembatan kereta api, hidrologi, hidrolika, tinggi jagaan, HSS Nakayasu, HEC-RAS.